PENGARUH MODAL INTELEKTUAL TERDAHAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Mohammad Herli; Hafidhah Hafidhah (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
This research is expected to be a reference for readers, especially corporate managementto pay attention to intellectual capital in encouraging the increase of company value. Thesample of this study consists of companies incorporated in LQ 45, the data collected andthen analyzed using regression and then the researchers do intrepretasi on the resultingoutput. The results showed that, intellectual capital affect the value of the company, thisis evidenced by the resulting significant value of 0.000 smaller than alpha 0.05. Theinfluence of intellectual capital in lifting company value indicates that companymanagement should pay attention to the management of intellectual capital within thecompany. Meanwhile, profitability variable which is the moderation variable in thisresearch also proves that the variable is able to moderate the relationship betweenintellectual capital and firm value.